Design and research of double stator magnetic field modulation permanent magnet motor - Weiliang Wu; Xiping Liu; Chaozhi Huang; Zhangqi Liu; Jianwei Liang (AIP Advances)
Permanent magnet motors (PM motors) are widely used in drive motor systems for electric vehicles due to their high power density and high torque density. In order to meet the various working conditions of electric vehicles, such as starting, braking, heavy-duty hill climbing, high-speed cruising, and frequent acceleration and deceleration, a dual-stator single-rotor magnetic field modulated permanent magnet synchronous motor (DS-FMPM) is designed, which utilizes the inner and outer electrical ports of the dual stator to achieve the cooperative excitation and multi-mode operation of the motor and focuses on the enhancement of the torque density, power density, and efficiency of the motor. It is verified by Ansys simulations and experiments that the proposed dual-stator magnetic field modulated permanent magnet motors with motor structures III and VI can flexibly control the power supply to the inner and outer stator windings of DS-FMPM motors, thus realizing multiple operation modes of the motors. This double-stator magnetic field modulated permanent magnet motor provides technical guarantee for the drive application of new energy electric vehicles.